FOOD PRICE VARIATIONS IN NUSA TENGGARA BARAT: EVIDENCE FROM RICE AND SHALLOT DATA (2024) - APRILIA SINTA ULI (Akademi Bisnis Lombok, 2025)
This study examines the dynamics of strategic food commodity prices, specifically C4 grade I quality rice and large clean quality shallots, across three key locations in Nusa Tenggara Barat Province during 2024. Utilizing a quantitative descriptive approach with secondary data from Statistics Indonesia (BPS) NTB, this research analyzes monthly price fluctuations, inter-regional variations, and stability patterns. Results indicate that rice prices averaged Rp14,780/kg in Mataram City, Rp15,447/kg in Bima City, and Rp15,361/kg in Sumbawa Regency, with coefficient of variation ranging from 6.2% to 8.0%. Shallot prices demonstrated greater volatility, averaging Rp32,266/kg annually with a price range of Rp19,006-41,736/kg. Mataram City consistently exhibited the most stable prices due to superior market infrastructure and distribution networks, while Bima City recorded the highest prices attributed to geographical factors and inter-island transportation costs. Seasonal patterns emerged clearly, with price peaks occurring during the lean season in the first quarter and before major religious holidays. The study recommends strengthening regional food security through optimized food reserve stocks, integrated logistics systems, and enhanced roles for regional food enterprises in price stabilization mechanisms.